Advances in biodegradable food packaging using wheat-based materials: fabrications and innovations, applications, potentials, and challenges - Alibekov, Ravshanbek S.; Urazbayeva, Klara U.; Azimov, Abdugani M.; Rozman, Azri Shahir; Hashim, Norhashila; Maringgal, Bernard (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This article explores the advancements in biodegradable food packaging materials derived from wheat. Wheat, a predominant global cereal crop, offers a sustainable alternative to conventional single-use plastics through its starch, gluten, and fiber components. This study highlights the fabrication processes of wheat-based materials, including solvent casting and extrusion, and their applications in enhancing the shelf life and quality of packaged foods. Recent innovations demonstrate effectiveness in maintaining food quality, controlling moisture content, and providing microbiological protection. Despite the promising potential, challenges such as moisture content and interfacial adhesion in composites remain.